Effects of 3D Contemplative Landscape Videos on Brain Activity in a Passive Exposure EEG Experiment - Olszewska-Guizzo, Agnieszka A.; Paiva, Tiago O.; Barbosa, Fernando (Frontiers in Psychiatry, 2018)
Background: Studies on Contemplative Landscapes (CL) show that not only do they have high ecological and visual values and are preferred by a majority of people, but they also can be beneficial to our mental health and well-being. Physical attributes of CL have been studied and operationalised, which has led to the development of the psychometric measurement tool called the Contemplative Landscape Questionnaire (CLQ) [1]. Objectives: In the present study, we applied an experimental approach to the analysis of CL. We hypothesized that, when compared to Non-Contemplative Landscapes (NCL), they would induce higher frontal alpha power asymmetry, higher temporal beta power asymmetry and lower bilateral frontal beta power. Methods: 32 healthy individuals (12 female) took part in the study. During the experimental protocol, participants were asked to passively view 12 landscapes, six CL and six NCL, while continuous EEG was recorded in a within-subjects design. Results: We found significantly increased power in the beta frequency band of the right temporal brain regions in the viewings of CL compared to NCL. Conclusions: The findings suggest that Contemplative Landscapes capture more visual, stimuli-driven attention from the viewers and can be linked with switching attention systems (described in Attention Restoration Theory), which is compatible with a stress reduction mechanism.